Peak exercise stroke volume effects on cognitive impairment in community‐dwelling people with preserved ejection fraction. (26th June 2018) - Sugie, Masamitsu; Harada, Kazumasa; Takahashi, Tetsuya; Nara, Marina; Kawai, Hisashi; Fujiwara, Yoshinori; Ishikawa, Joji; Tanaka, Jun; Koyama, Teruyuki; Kim, Hunkyung; Sengoku, Renpei; Fujimoto, Hajime; et al.
Abstract: Aims: The association of vascular dysfunction and amyloid beta deposition attracted attentions for its relationship with cognitive decline. Previous studies show the correlation between the declined cardiac function and the cognitive impairment. In the present study, we analysed the association between cognitive functions and cardiac parameters in community‐dwelling people with preserved ejection fraction without heart failure. Methods and results: Subjects were 108 Japanese community‐dwelling middle‐aged and older adults with preserved ejection fraction (25 men and 83 women; mean age 74.7 years). Cardiac functional parameters at rest were assessed with B‐type natriuretic peptide and echocardiography. The cardiopulmonary exercise test was used to test these parameters during exercise. Cognitive function was assessed with the Japanese version of the Montreal Cognitive Assessment (MoCA‐J). Other indices were assessed biochemically, physiologically, and physically. There were significant correlations between MoCA‐J score and age ( r = −0.388), peak oxygen uptake (VO2, r = 0.201), peak VO2 /heart rate (HR, r = 0.243), peak VO2 /weight ( r = 0.244), peak metabolic equivalents ( r = 0.244), usual walking speed ( r = −0.200), and the Timed Up and Go test ( r = −0.230). Multiple linear regression analysis showed peak VO2 /HR was an independent determinant of MoCA‐J score after adjusting for potential confounders ( B = 0.424). After 6 months of exercise training with 64 subjects, we found that the per cent change of peak VO2 /HR was related to the per cent change of MoCA‐J score ( r = 0.296). Conclusions: These results suggested that peak VO2 /HR (an index of stroke volume at peak exercise) might be associated with cognitive impairment based on the vascular cascade hypothesis.